#### Answer

$-\frac{36}{x}$

#### Work Step by Step

$-3x\div\frac{x^2}{12}=\frac{-3x}{1}\times\frac{12}{x^2}=\frac{-3x\times12}{1\times x^2}=\frac{-36x}{x^2}=\frac{-36x\div x}{x^2\div x}=\frac{-36}{x}=-\frac{36}{x}$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

$-\frac{36}{x}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.